A COVID-19 outbreak among migrants in a hosting facility in Greece, April 2020. Issue 5 (September 2022) - Mellou, Kassiani; Gkolfinopoulou, Kassiani; Andreopoulou, Anastasia; Tsekou, Aikaterini; Papadima, Kalliopi; Stamoulis, Konstantinos; Kossyvakis, Athanasios; Mentis, Andreas; Maltezou, Helena C
In April 2020, a coronavirus disease 2019 outbreak was identified among migrants/refugees in Greece. Overall, 155 of 450 hosted migrants and two of 46 employees were infected (attack rates: 34.4% and 4.3%, respectively). The mean age of infected migrants was 24.9 years (3 days-68 years). In addition, 177 community contacts were tested negative. Cases were cohorted in separate rooms from people tested negative. Surfaces were cleaned and disinfected daily. The implementation of measures for the containment of the outbreak was challenging due to language barriers and lack of space for cohorting. At that time, there was no official recommendation to the general population regarding the use of masks or other personal protective equipment. Extensive testing of vulnerable populations and building trust in order to report symptoms and comply with the recommendations are essential.